The barriers to therapeutic communication in psychiatric wards: a focused ethnography - Zahra Raisi; Sedigheh Khodabandeh Shahraki; Behnaz Bagherian; Nahid Dehghan Nayeri (BMC Nursing)
Abstract Background and aim Identifying the influential factors affecting effective nurse-patient communication in psychiatric wards may facilitate the development of strategies to enhance communication. The aim of this study was to explore the barriers to therapeutic communication (TC) in psychiatric wards. Methods This qualitative study was conducted in 2022 using Spradley’s focused ethnography. Participants included 32 nurses, auxiliary nurses, psychologists, physicians, nursing managers, patients, and patient companions purposively selected from the emergency wards of a psychiatric hospital in Iran. Data were collected through observations, interviews, field notes, and fieldwork journals and were analyzed using Spradley’s method. Findings Four main cultural themes emerged from the 47 codes on TC barriers in psychiatric wards: different worlds of care, inappropriate portrayals of clinical interactions with patients, stressful care environments, and sociocultural norms. These cultural themes encompassed twelve cultural components. Conclusion A broad range of nurse-related, patient-related, environmental, and sociocultural factors may act as barriers to TC in psychiatric wards. Study findings can be utilized to develop strategies for managing the barriers to TC in psychiatric wards.